ДО ПИТАННЯ ПРО РЕГУЛЮВАННЯ ВІДНОСИН БІЗНЕСА І ВЛАДИ НА РІВНІ ДЕРЖАВИ, РЕГІОНУ, МІСЦЕВОГО САМОВРЯДУВАННЯ - Buleev, I.P. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2010)
Forms and methods of business and power cooperation on the level of state, region, territorial communities are well-grounded. It is proved that it is not possible to separate business from power. The expediency of realizing the notion «urban economic management» as one of the forms of business and power cooperation is supported.